Traumatic Cervical Spinal Cord Injury: Correlation of Imaging Findings with Neurological Outcome - Yousefzadeh-Chabok, Shahrokh; Asadi, Khatereh; Jahanbakhsh, Javid; Rad, Enayatollah Homaie; Reihanian, Zoheir; Modaenama, Morteza (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Background Traumatic spinal cord injury (TSCI) is extremely costly to the global health system. Due to the significant frequency rate of traumatic cervical spinal cord injuries (TCSCI), the possible association between imaging findings and clinical outcome is not yet clear. In this study, we quantified maximum spinal cord compression and maximum cord swelling following TCSCI and determined the relevance of imaging findings to clinical outcome in patients.Materials and Methods This retrospective cohort comprises 20 patients with TCSCIs (C3-C7), classified as complete, incomplete, and no SCI, who were treated at the Poursina Hospital, Iran, from 2018 to 2020, and underwent spinal surgery. Patients with penetrating injuries and multiple trauma were excluded. Imaging findings revealing spinal cord compression, swelling, and canal stenosis, based on the American Spinal Injury Association (ASIA) Impairment Scale (AIS) grades of patients from hospital admission (up to 48 hours after injury) and improvement of postoperative neurological symptoms (6–12 months) were evaluated.Results Cord compression (p = 0.05) and cord swelling (p = 0.02) were significantly related to predictive neurological outcomes in all cases. Evaluation with AIS at hospital admission and at 6 to 12 months postoperatively showed significant correlation with fracture type (p = 0.05) and the longitudinal length of the intramedullary lesion (IML); p = 0.01, respectively.Conclusion According to the results obtained in this study, it may be concluded that there is a significant association between cervical spinal cord compression and swelling, and clinical outcomes in patients with complete, incomplete, and no SCI.IntroduçãoA lesão traumática da medula espinal (LTME) é extremamente onerosa para o sistema de saúde global. Devido à significativa taxa de frequência de lesões traumáticas da medula espinal cervical (TCSCI), a possível associação entre achados de imagem e evolução clínica ainda não está clara. Neste estudo, quantificamos a compressão medular máxima e o edema medular máximo após TCSCI e determinamos a relevância dos achados de imagem para o resultado clínico dos pacientes.Materiais e métodos Esta coorte retrospectiva compreende 20 pacientes com TCSCIs (C3-C7), classificados como completos, incompletos e sem LME, que foram tratados no Hospital Poursina, Irã, de 2018 a 2020, e submetidos a cirurgia da coluna vertebral. Pacientes com lesões penetrantes e politraumatismos foram excluídos. Achados de imagem revelando compressão da medula espinhal, edema e estenose do canal, com base nos graus da American Spinal Injury Association (ASIA) Impairment Scale (AIS) de pacientes desde a admissão hospitalar (até 48 horas após a lesão) e melhora dos sintomas neurológicos pós-operatórios (6-12 meses) foram avaliados.Resultados A compressão do cordão (p ≡ 0,05( e o edema do cordão (p ≡ 0,02) foram significativamente relacionados aos desfechos neurológicos preditivos em todos os casos. A avaliação com AIS na admissão hospitalar com 6 a 12 meses de pós-operatório mostrou correlação significativa com o tipo de fratura (p ≡ 0,05) e o comprimento longitudinal da lesão intramedular (IML); p ≡ 0,01, respectivamente.Conclusão De acordo com os resultados obtidos neste estudo, pode-se concluir que existe uma associação significativa entre compressão e edema da medula espinal cervical e desfechos clínicos em pacientes com lesão medular completa, incompleta e sem lesão medular.
Keywords: traumatic cervical spinal cord injury; imaging findings; neurological outcome